Sosialisasi Penerapan Rekam Medis Elektronik sebagai Upaya Peningkatan Kesiapan Kompetensi Digital Mahasiswa Kesehatan pada Praktik Klinik: Socialization of Electronic Medical Record Implementation as a Strategy to Enhance Digital Competency among Health Students during Clinical Practice - Raharjo, Untoro Dwi; Sukmawati, Anastasia Suci; Sari, Rizky Yuspita; Sevtiyani, Imaniar (Universitas 45 Surabaya, 2025)
Electronic Medical Records (EMR) is an important health information system for improving efficiency and service quality. In Indonesia, the implementation of EMR still faces challenges such as the lack of readiness and understanding of EMR among healthcare professionals, including students, resulting in considerable resistance to EMR adoption. The EMR socialization activities at the Faculty of Health, Universitas Jenderal Achmad Yani Yogyakarta, aim to enhance students' understanding of EMR and address implementation challenges. These activities involve 22 students from the Medical Records and Health Information (D-3), Nursing (S-1), and Pharmacy (S-1) programs. The socialization material was delivered through interactive approach and discussions, followed by a post-test using the Technology Readiness Index (TRI) questionnaire. The EMR socialization was successfully introducing the basic concepts of EMR to students. Before the socialization, most students were not familiar with EMR and were still using manual medical records. After the socialization, there was a positive readiness for EMR, reflected in students' positive views on the efficiency, effectiveness, and creativity of working with EMR. Continuous capacity-building activities related to EMR for students are necessary.